Two-Dimensional Signal Detection Algorithm for Omni-Directional Signal Receiving Using Low-Frequency Orthogonal Magnetic Antenna - Feng, S. M.; Wang, S. Y.; Wang, L. F. (Radioengineering, 2022)
This paper proposes a two-dimensional signal detection algorithm for low-frequency signal receiving using orthogonal magnetic antenna. According to the directional properties of a single antenna, the direction coefficient is introduced into the model. The algorithm based on Markov Chain Monte Carlo (MCMC) method can accurately estimate the direction coefficient and parameters of the noise in order to perform signal detection. The results show that the proposed algorithm is less affected by the direction of arrival and performs better, in terms of bit error rate, than that based on one-dimensional model. This study provides a valuable reference to omni-directional receiving of signals in low-frequency communication.